Efecto citotóxico y genotóxico de nanopartículas de cobre sobre el ciclo celular en meristemos radiculares de Allium cepa “cebolla” - ESCOBEDO PAREDES, Cristhian Rafael (2019)
Copper nanoparticles (NPsCu) have been of important interest due to the antimicrobial and antifungal properties that they possess, however, the excessive presence of copper has also proven to be toxic to cellular organisms in general, so the present research aimed determine the cytotoxic and genotoxic effect of copper nanoparticles obtained by laser ablation on the cell cycle in root meristems of Allium cepa "onion." The execution was carried out in the Cytometry Laboratory and the Laboratory of Optics and Lasers of the National University of Trujillo. Bulbs of A. cepa were selected with rootlets of average length of 2.5 cm, which were exposed to the concentrations of 0, 25, 50 and 100% NPsCu, constituting the treatments T1, T2, T3 and T4 respectively. The mitotic index, phase index and the hereditary material anomaly index were evaluated. A completely randomized experimental design was applied, with three repetitions for each of the four treatments. Data were analyzed by ANOVA tests and comparison of means. The results obtained show that the T4 treatment (100% NPsCu) caused the greatest reduction in the mitotic, metaphase and anaphase index, both for one and four hours of recovery; in the latter, it also produced the greatest reduction of the telophasic index. The T4 treatment caused a significant increase in the prophase index, for one and four hours of recovery. A genotoxic effect was observed with the presence of hereditary material anomalies such as anaphase bridges, binucleated cells and amorphous telophases.